Temperature data recorded with Thermochron iButton data loggers in 2018 in Hengill, a sub-arctic geothermal area in SW-Iceland (64°03’N; 21°18’W, ~360 m.a.s.l.) - Ehrlén, Johan; Valdés, Alicia; Helmutsdóttir, Vigdís F.; Marteinsdóttir, Bryndís (Stockholm University, 2022)
This data set includes temperature data recorded with Thermochron iButton data loggers in 2018. The data comprises 40 pairs of data loggers of which one was located belowground (buried at 10 cm depth) in order to measure soil temperature, and one was located aboveground (10 cm aboveground, on the top of white plastic tubes stuck in the ground, and covered with grey duct tape) in order to measure air temperature. The loggers recorded temperature every 3 hours from October 2017 until June 5th, 2018. The data also includes a measure of instant soil temperature measured in May at the same point where the pair of loggers was located.
Keywords: Terrestrial ecology; Evolutionary ecology; Ecology; Ekologi